STUDI KEPUTUSAN MENGINAP DI SEKURO VILLAGE BEACH RESORT JEPARA: DENGAN PENGARUH PROMOSI, E-COMMERCE & BRAND IMAGE - Setyo Legowo; Andhi Supriyadi (LPSDI Bina Patria, 2025)
The purpose of this research is to study how promotions, e-commerce, and brand image influence guests' decisions to stay at Sekuro Village Beach Resort Jepara. This study is inferential research that focuses on the analysis of numerical data that has been processed using statistical techniques, with the aim of evaluating the influence of promotions, E-commerce, and Brand Image on guests' decisions to stay at Sekuro Village Beach Resort Jepara. This study involved 98 guests staying at Sekuro Village Resort Jepara Park as research respondents. The data collection method is a questionnaire; after that, the data was tested and analyzed using multiple linear regression using SPSS. According to research data analysis, it can be concluded that Promotion, E-Commerce, and Brand Image influence the decision to stay. From this research, it can also be suggested that Sekuro Village Beach Resort Jepara increase promotions and utilize E-commerce so that the brand image can increase and influence guests' decisions to stay.